Efeitos da técnica breath stacking após cirurgia abdominal alta: ensaio clínico randomizado - Fernandes, Débora da Luz (2020)
Introduction: Upper abdominal surgery is used for the diagnosis and treatment of several diseases or dysfunctions, but it can lead to postoperative pulmonary complications. Physiotherapy uses techniques, such as Breath Stacking (BS), that promote pulmonary reexpansion and prevent relevant outcomes. Objective: To evaluate the effects of BS on lung function, vital signs, peripheral oxygenation, thoracoabdominal mobility and pain in the surgical incision in the postoperative period (PO) of upper abdominal surgery (UAS) and analyze BS security. Method: Randomized clinical trial that took place at the General Surgery Unit, University Hospital of Santa Maria, Santa Maria - RS. Subjects undergoing upper abdominal surgery were recruited. They were randomized to the group which received conventional physical therapy associated with BS (BSG; n=18) and to the control group (CG; n=16) which received only conventional physical therapy. The primary end points were forced vital capacity (FVC) and tidal volume (TV). Secondary outcomes were: vital signs, peripheral oxygen saturation, thoracoabdominal mobility, painful perception in the surgical incision, lung volumes and capacities and maximum respiratory pressures. BS safety was assessed by the incidence of gastrointestinal, hemodynamic and respiratory repercussions. The evaluations took place on the 2nd day from PO (between 24 and 48 hours after surgery) and at hospital discharge. Both groups had two daily sessions, from the 2nd day PO until hospital discharge. BS was applied in two daily sessions of up to 20 min. GraphPad Prism 5 program was used for data analysis. The variables with normal distribution were analyzed by parametric tests and those with asymmetric distribution by non-parametric tests. The test was accepted by the UFSM Ethics and Research Committee and registered in the Clinical Trials (NCT04418700). Results: The mean age was 53 years in the CG and 46 in the GBS. FVC increased in both groups at hospital discharge, with a greater effect on BSG. FEV1, FEV1 / FVC, PEF and FEF25-75% increased only in BSG, with an effect superior to that of CG. The minute volume and TV increased in the BSG, but without differing from the CG. MIP and MEP increased in both groups, with a greater effect on BSG. Reduction of respiratory rate (RR) and increase of SpO2 only in BSG. SpO2 increased after BS, however, without changes in the degree of dyspnea and vital signs withoutsigns of respiratory distress or gastrointestinal and hemodynamic repercussions. Conclusion: BS is safe and effective for recovering lung function, peripheral oxygenation and reducing respiratory work in the PO of UAS.